2015
DOI: 10.3109/07435800.2015.1038352
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid-rich diet suppresses glucose-stimulated insulin secretion (GSIS) and induces endoplasmic reticulum (ER) stress in pancreatic islets in mice

Abstract: The objective was to clarify whether dietary palmitic acid supplementation affects glucose-stimulated insulin secretion (GSIS) and the endoplasmic reticulum (ER) stress pathway in pancreatic islets in mice. Eight-week-old male C57BL/6J mice were randomly divided into three treatment diet groups: control diet, palmitic acid-supplemented diet (PAL) and oleic acid-supplemented diet (OLE). After 2 weeks of treatment, intraperitoneal glucose tolerance test and intraperitoneal insulin tolerance test were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
3
14
1
Order By: Relevance
“…Previously, we have shown that a palmitic acid-supplemented diet might cause deterioration of glucose tolerance by suppression of insulin secretion from pancreatic β cells in mice [8]. However, there was no difference in the level of palmitic acid among the normal, IGT, and diabetic groups in the current human study (Figure 4).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Previously, we have shown that a palmitic acid-supplemented diet might cause deterioration of glucose tolerance by suppression of insulin secretion from pancreatic β cells in mice [8]. However, there was no difference in the level of palmitic acid among the normal, IGT, and diabetic groups in the current human study (Figure 4).…”
Section: Discussioncontrasting
confidence: 52%
“…Recently, the effects of FFAs on insulin's action have been investigated intensively [5, 6]. We have previously shown that FFAs cause β cell damage mainly by apoptosis in vitro [7] and by ER stress in mice [8]. The serum composition of FFAs in humans differs from race to race, and from environment to environment, because it reflects the average fat intake in the preceding days [912].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation with palmitate for 2 weeks upregulated ER stress markers in mouse Langerhans islets and suppressed glucose-stimulated insulin secretion (GSIS). CHOP, Bip, and XBP1 transcripts were all upregulated [ 70 ]. MIN6 β-cells are exposed to palmitate undergo apoptosis, which is potentiated by XBP1 inhibition [ 71 ].…”
Section: Er Stress Induces Ir and Diabetesmentioning
confidence: 99%
“…Dietary supplementation with palmitate for 2 weeks upregulated ER stress markers in mouse Langerhans islets and suppressed glucose-stimulated insulin secretion (GSIS). CHOP, BIP and XBP1 transcripts were all up regulated [66]. MIN6 β-cells exposed to palmitate undergo apoptosis, which is potentiated by XBP1 inhibition [67].…”
Section: Lipotoxicitymentioning
confidence: 92%